Effects of cadmium in plants of Sphagneticola trilobata (L.) Pruski (Bioagro, 2020)
Cadmium (Cd2+) is a pollutant of great environmental concern due to its multiple origins (natural and anthropogenic), the ability to accumulate in organs and tissues, and the deleterious effects it can cause in organisms. In the present study, we investigated the effects of Cd2+ exposure on Sphagneticola trilobata plants. We evaluated the accumulation of Cd2+, the plant biomass, the content of chlorophyll, soluble sugars, proteins and the production of malondialdehyde and thiols as markers of oxidative stress and tolerance, respectively. The Cd2+ content in the plant organs increased proportionally to the concentration of CdCl2 in the environment, reaching accumulatively 1306, 193 and 52 mg·kg-1 in roots, stems and leaves, respectively. Some toxic effects such as a decrease in the root biomass, alterations in the polypeptide pattern of the leaves, reduction in the chlorophyll content, and an increase in the amount of malondialdehyde was observed at higher concentrations of CdCl2. An increase in the content of soluble sugars was also seen, which are markers of tolerance associated with a protection mechanism against the oxidative stress. In addition, an increase on heavy metals chelating thiols such as L-cysteine, glutathione and various phytochelatins was obtained in the plant roots. Our results demonstrated that S. trilobata is capable of accumulating Cd2+ and possesses tolerance mechanisms that make this plant an excellent option to be used for Cd2+ phytoremediation.
Keywords: Glutathione; oxidative stress; phytochelatins; phytoremediation; tolerant plants; wedelia